Indian nurses’ Knowledge, Attitude and Practice towards use of physical restraints in psychiatric patients - Sailaxmi Gandhi; Vijayalakshmi Poreddi; - Nagarajaiah; Marimutthu Palaniappan; S. Sai Nikhil Reddy; Suresh BadaMath (Investigación y Educación en Enfermería, 2018)
Objective. To assess nurses’ knowledge, attitude and practice towards using physical restraints among psychiatric patients.